219-13FR Sacha inchi oil-based nanoemulsion of bay leaf (syzygium polyanthum) and binahong leaf (anredera cordifolia) extracts and in vitro release using a dialysis membrane - Dudy Agustian Hidayat; Garnadi Jafar; Winasih Rachmawati; Rieztya Aliza; Sulthan Abdul Basith Ratmoko (Science Midwifery, 2026)
This study aimed to develop and characterize a nanoemulsion system containing combined extracts of bay leaf (Syzygium polyanthum) and binahong leaf (Anredera cordifolia) using sacha inchi oil, and to evaluate its in vitro release profile using a dialysis membrane method. The extracts were prepared by maceration using 96% ethanol and characterized through physicochemical and phytochemical analyses. Nanoemulsions were formulated using Cremophor RH40 and PEG 400, followed by homogenization and sonication. The formulations were evaluated for particle size, polydispersity index (PDI), zeta potential, and morphology. The results showed that the optimized formulation (NEC5) exhibited the smallest particle size (130.06 ± 56.66 nm), acceptable PDI (0.45 ± 0.12), and moderate zeta potential (−14.15 ± 4.88 mV), indicating good stability. Morphological analysis confirmed spherical and uniformly distributed droplets. In vitro release studies demonstrated an initial burst release followed by a more controlled release pattern, with the nanoemulsion showing more stable release compared to the extract. In conclusion, the nanoemulsion system successfully improved the physicochemical properties and controlled release behavior of the plant extracts, indicating its potential as an effective delivery system for plant-derived bioactive compounds.